Non-speech information w angielskich i rosyjskich napisach Closed Captions zawartych w serialu Эпидемия. Analiza kontrastywna - Piecewicz, Daniel (Studia Rossica Posnaniensia, 2023)
The article focuses on a specific and little explored branch of audiovisual translation, namely non-speech information (Zdenek, 2015) in the Closed Captions (CC) in the Netflix production series To the lake (Russian title Эпидемия), directed by Pavel Kostomarov. The article attempts to reach a consensus in the terminological dispute between the countries of North America and Oceania (Captions) on the one hand, and the countries of Europe on the other (Subtitles). The decision to use the term “captions” and “captioning” is being justified. The method used in the research is the corpus-driven method, and the contrastive method between the intralingual captions in Russian and the interlingual captions in English. Individual types of non-speech information are compared: Speaker identifier, Language identifier, Sound effects, Paralanguage, Manner of speaking identifiers, Music and Channel identifier (Zdenek, 2015). In addition, some space is devoted to the NSI as non-verbatim. The results show a slight discrepancy in the amount of NSI used (2,020 in the English version and 2,004 in the Russian version). The greatest disproportions are noticed only at the level of individual categories. Differences were noticed, among others, in the level of the originality of data records, i.e. greater synonymy in the English version, especially in the category of Paralanguage and Sound effects. The research opens up a discussion on the condition of captions and improving accessibility in the NSI usage.